2022
DOI: 10.3390/jcm11185393
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Phaeohyphomycosis of Curvularia lunata

Abstract: Originally considered to be a plant pathogen, reports of phaeohyphomycosis due to Curvularia lunata (C. lunata) in animals and humans are increasing. However, studies on the pathogenesis, virulence, and epidemiology of C. lunata have rarely been discussed. In the present study, BALB/c mice were experimentally inoculated with C. lunata suspension by different routes and the course of infection was evaluated. In addition, the in vitro antifungal susceptibility of C. lunata against six commonly used antifungals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Wang et al demonstrated that C. lunata is sensitive to itraconazole, voriconazole, and amphotericin B, while resistant to 5-fluorocytosine and fluconazole (Wang et al, 2014). In vitro susceptibility studies suggested that treatment with amphotericin B, miconazole, ketoconazole, fluconazole, and itraconazole may be effective (Al-Odaini et al, 2022). A consensus regarding the optimal antifungal treatment for C. lunata has not been reached.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al demonstrated that C. lunata is sensitive to itraconazole, voriconazole, and amphotericin B, while resistant to 5-fluorocytosine and fluconazole (Wang et al, 2014). In vitro susceptibility studies suggested that treatment with amphotericin B, miconazole, ketoconazole, fluconazole, and itraconazole may be effective (Al-Odaini et al, 2022). A consensus regarding the optimal antifungal treatment for C. lunata has not been reached.…”
Section: Discussionmentioning
confidence: 99%
“…Limited knowledge is available about the susceptibility and resistance of eumycetoma causing agents, and the lack of available CLSI criteria for C. lunata often leads to delayed and prolonged treatment (Dubey et al, 2019 ; Al-Odaini et al, 2022 ). The primary management of eumycetoma are surgical debridement along with systemic antifungals (Agarwal et al, 2021 ).…”
Section: The High Priority Group From the Who Fpplmentioning
confidence: 99%
“…Different antifungal agents have very diverse effects on C. lunata . Based on checkerboard broth microdilution method VRC was the most effective, while terbinafine, AMB, ITC and ketoconazole had moderate activity, and FLC was the least efficient antifungal agent (Al-Odaini et al, 2022 ). Agarwal et al ( 2021 ) reported that terbinafine is effective only in combination with ITC; VRC and POS have both good in vitro activity, while echinocandins and AMB have poor in vitro outcome.…”
Section: The High Priority Group From the Who Fpplmentioning
confidence: 99%
“…The melanin precursors in fungi and yeast are secreted and subsequently oxidized exterior of the cell wall [ 2 ]. Some Curvularia species, which are dematiaceous fungi, are capable of synthesizing melanin which shows a vital function in the virulence and pathogenicity of these fungi [ 9 ]. Studying melanin production and the selection of new, atypical sources are critical because of the increased need for the melanin pigment.…”
Section: Introductionmentioning
confidence: 99%